Efecto del manejo cultural de un sistema de mezcla intraespecífica de musáceas sobre la incidencia y severidad de los principales problemas fitosanitarios. - Navarrete Carrera, Leonardo Alexander (2017)
The effect of the cultural management of a system of intraspecific mixture of musaceae on the incidence and severity of the main phytosanitary problems was carried out with the objective of evaluating the main phytosanitary problems in musaceae during the high pressure period, in the different arrangements of Intraspecific mixtures, establishing the intensity of phytosanitary problems (Black Sigatoka, Black Batshop and nematodes) in production systems with intraspecific mixtures and to determine the effect of cultural management on the intensity of banana phytosanitary problems with an intraspecific mixing system of musaceae . The research was carried out on the experimental farm "La María" owned by Quevedo State Technical University, located in Quevedo Canton, Province of Los Ríos. A completely randomized design, composed of 4 replicates and 16 treatments, was analyzed statistically by the Tukey test (p≤0.05) to establish the statistical difference between the treatments. The variables that were taken into account were incidence of M. fijiensis disease, damages caused by black boll weevil, nematode damage and yield. With the results the following conclusions were established: The use of intraspecific mixtures of musaceae does not represent any difficulty to the small producer in terms of crop management; in addition, there was no difference in their physiology in the cultivars used in the mixtures, the effect of Biodiversity with the use of intraspecific blends of musaceae was observed to reduce phytosanitary problems; In Black Sigatoka the mixture that most stood out was Orito + Limeño, while in Black Picudo the mixture less damage was Gross Michel + Orito, one of the advantages through the use of intraspecific mixtures and that is very related to the proposal of this project Of research is to keep the cultivars on the verge of extinction, since they are not used by small producers as a product due to their economic value. Key words: Muses, Intraspecific, Biodiversity, Diseases.